A Rejoinder regarding Veronika Six’s Review Published in Aethiopica, 22 (2019), 271–276 - Nosnitsin, Denis (Aethiopica, 2020)
The rejoinder responds to a review, penned by Dr Veronika Six, of a recent catalogue of Ethiopic manuscripts kept in Det Kongelige Bibliotek, Copenhagen, compiled by Dr Denis Nosnitsin. The rejoinder contains an exchange of arguments on the properties of the catalogue and responds to some critical remarks of V. Six. The dialog concerns individual characteristics of some specific manuscripts but also raises a number of issues and questions regarding some fundamental aspects of the cataloguing practice.